ANALISIS PENGARUH KEBIJAKAN HEDGING DENGAN INSTRUMEN DERIVATIF VALUTA ASING DAN VARIABEL-VARIABEL VALUE DRIVERS TERHADAP NILAI KEKAYAAN PEMEGANG SAHAM (Studi Empiris Terhadap Perusahaan Nonfinansial yang Terdaftar di Bursa Efek Jakarta tahun 2000-2003) - Paranita, Ekayana Sangkasari (JURNAL BISNIS STRATEGI, 2006)
The fluctuation of foreign currency exchange has given a negative influence towards cash flow and firm's value, and it also threats the related-company survive. In the other hand, the company obligates to maximize the shareholder's value. Therefore, to anticipate the negative influence of foreign exchange fluctuation and also to prevent it for the shareholder's importance, thus partly firms have done a hedging policy with foreign exchange derivative instrument. This research has been done to achieve the implication of good managerial both for the investors or the management.This research aims to analyze the influence of hedging policy and foreign exchangederivative instrument towards the shareholder's value with value-drivers control variables. The shareholders value uses Market-to-Book Value of Equity ratio (MBE) indicator. The hedging policy is reflected dummy variable. Whereas the variable control that is used is Total Asset Turnover (TAT), Operating Profit Margin (OPM), Net Fixed Asset to Total Asset (NFA TA), Current Ration (CR), and Debt to Equity Ratio (DER). The type of data that is used is secondary data that gained from !GMO 2003 - 2004 and JAKARTA STOCK EXCHANGE web site. The research population is the whole non-financed companies in JAKARTA STOCK EXCHANGE. The purposive sampling with full sample method gains 104 emitters as the sample during the period of 2000 - 2003. This research uses regression analysis with Least Square Dummy Variable (LSDV) model. The hypothesis test uses t test and F test with 5 % significant level. This research result shows that the hedging policy with foreign exchange derivative instrument in JAKARTA STOCK EXCHANGE does not influence the shareholders value. This is caused by the characteristic of JAKARTA STOCK EXCHANGE that have emerging market characteristic, whereas the United States' stock exchange has developed market characteristic. Then the whole of control variables both partiallyor simultanly contributes a significant influence towards the increasing of shareholders value.